The Monotone Contraction Mapping Theorem - Joseph Frank Gordon (Journal of Mathematics)
In this paper, the fixed-point theorem for monotone contraction mappings in the setting of a uniformly convex smooth Banach space is studied. This paper provides a version of the Banach fixed-point theorem in a complete metric space.